Banking Competition and Market Efficiency - Yanelle, Marie-Odile (Review of Economic Studies, 1997)
This paper analyses competition among financial intermediaries in a set-up where financial intermediaries economize on duplicated monitoring (Diamond (1984)). We analyse two different games in which both direct trade and indirect trade are available. We show that in general equilibrium outcomes are inefficient, so that Diamond's efficiency result is fragile. Intermediation may increase rather than decrease transaction costs. Disintermediation may also be an equilibrium. We discuss the role played by the nonconvexities of banks' technology and that played by competition for deposits and loans.